The Effect Of Taxes, Tunneling Incentives, Bonus Mechanism, Leverage On Transfer Pricing - Maryanti, C. Susi; Agus Munandar (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
This study examines the effect of taxes, tunnelling incentives, bonus mechanisms and leverage on transfer pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study population included listed manufacturing companies on IDX from 2017 to 2021 and had their financial statements published on the IDX. The sampling technique used was purposive sampling, taking thirteen companies with a study period of five years, thus obtaining a total of sixty-five study samples. The statistics used in this examination are taken from the company's financial statements. This study uses a quantitative design combined with data analysis techniques using classical hypothesis testing, descriptive statistics testing and hypothesis testing. The results show that tax, tunnelling incentive and leverage variables significantly impact the transfer pricing indication. The bonus mechanism variable has no impact on the indication of transfer pricing.